Disability-adjusted life years for respiratory syncytial virus in children under 2 years (2020)
ABSTRACT: Background: Respiratory syncytial virus infection is the leading cause of bronchiolitis in Colombia. There is growing evidence about the impact of Respiratory syncytial virus on society in terms of years of life lost due to this condition. The objective of the present study is to determine the Disability-Adjusted Life Years for respiratory syncytial virus in children under 2 years in Colombia. Methods: Data from the national epidemiological surveillance system were used to estimate DALYs, calculated from the sum of years of life lost and years lived with disability due to RSV infection in Colombia. A bootstrapped method with 10,000 iterations was used to estimate each statistical parameter using the package DALY calculator in R. Results: In 2019, 260,873 years of life (CI95% 208,180–347,023) were lost due to RSV bronchiolitis in Colombian children under 2 years. The estimated rate was 20 DALYs / 1000 person-year (95% CI 16–27). Conclusion: This is the first report estimating the impact of RSV bronchiolitis morbidity and mortality in Colombia. The findings of the present study suggest that the actual burden and cost of bronchiolitis due to RSV is high. Prevention strategies, such as RSV vaccination, to reduce morbidity associated with RSV infection should be encouraged in our country.